(untitled) (Scientific journal of the Fergana State University, 2023)
In Uzbek linguistics there are such types of comparative simple sentences as pure comparative and analogical simple sentences. The location and syntactic position of the comparative elements in the structure of these sentence types has a peculiarly complex character.